URGENSI PENYELESAIAN SENGKETA PILKADA OLEH MAHKAMAH KONSTITUSI - Ida Puspa Jaya Miha (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2015)
The rise of the disputed local elections assessed due to poor direct voting system that alwaysend with anarchic conflict. Direct voting system is briefly diverted to be chosen by the Houseof Representatives (DPR) through Law 22 of 2014 concerning Election of Governors,Regents and Mayors but this law received widespread rejection by the people so that thePresident issued Government Regulation in Lieu of Law No. 1 of 2014 which regulates thesame things that later passed into Law No. 1 of 2015. Article 157 paragraph (1) of Law No.8 of 2015 on the Amendment of Act No. 1 of 2015 mandates the establishment of a specialtribunal to deal with the settlement of disputes nationwide simultaneous election to be heldin 2027. If the judiciary is not yet formed, the implementation of election dispute resolutionmade by the Constitutional Court (MK). Based on the description above background, asfor the formulation of the problem to be studied is; What advantages and disadvantages ofthe establishment of a special judicial body which handles dispute resolution election? Andwhat is the urgency of the election dispute resolution by the Constitutional Court? This typeof research is a kind of normative legal research descriptive analysis using the approach oflegislation, the legal concept analysis approach, historical approach, and the approach ofcase law derived from the source material of primary, secondary and tertiary using a cardsystem as its legal material collection technique.The conclusion of this study is the establishment of a special judicial body has advantagesand disadvantages. The drawback is; unconstitutional existence of the judicial authoritiesfor not guided by Article 24 paragraph (1) of the 1945 Constitution and Article 27 paragraph(1) of Act 48 of 2009 on Judicial Power, the magnitude of the amount of the budget that willbe issued by the state to establish such institutions. The advantage is ease the burden on theMK, more focused and rapid election dispute resolution process.